2015
DOI: 10.1007/s00436-015-4492-1
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 promotes Th2 immune responses in infected mice with Schistosoma japonicum

Abstract: IL-33, a new member of the IL-1 cytokine family, is associated with many infectious diseases. IL-33 not only is crucial for induction of Th2 polarized responses, but also is involved in induction of inflammation as a proinflammatory cytokine. Whether IL-33 leads to beneficial or worsening outcomes depends on the immune mechanism underlying the pathogensis of each disease condition. This study was to elucidate the role of IL-33 in schistosomiasis japonica in a mouse model. Our results demonstrated that serum le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…81 IL-33 enhanced periodontal bone loss in Porphyromonas gingivalis infected mice through up-regulated receptor activator of NF-κB ligand expression in B and T lymphocytes in gingival mucosa, 82 which was abolished in ST2 knockout mice. In parasitic infections, IL-33 sensitized the mice to increased T H 2 response and liver disease caused by Schistosoma japonicum, 83 and antagonizing the IL-33 proved protective. The visceral leishmaniasis by Leishmania donovani was enhanced by IL-33 administration by blocking T H 1 cytokines and liver infiltration of leukocytes.…”
Section: Exacerbating Role Of Il-33 In Various Diseasesmentioning
confidence: 99%
“…81 IL-33 enhanced periodontal bone loss in Porphyromonas gingivalis infected mice through up-regulated receptor activator of NF-κB ligand expression in B and T lymphocytes in gingival mucosa, 82 which was abolished in ST2 knockout mice. In parasitic infections, IL-33 sensitized the mice to increased T H 2 response and liver disease caused by Schistosoma japonicum, 83 and antagonizing the IL-33 proved protective. The visceral leishmaniasis by Leishmania donovani was enhanced by IL-33 administration by blocking T H 1 cytokines and liver infiltration of leukocytes.…”
Section: Exacerbating Role Of Il-33 In Various Diseasesmentioning
confidence: 99%
“…IL-33 de ciency does not affect S. mansoni worm maturation, reproduction, and egg excretion Schistosome worms are characterized by their dependence on the host immune system, particularly type 2 immunity, for their maturation, reproduction, and egg excretion (14,17,34,36), pointing to the importance of type 2 immunity in the biology of schistosomes. Because IL-33 is known to induce type 2 immunity independently of IL-4 (37), and that a recent study (25) reported increased S. japonicum worm numbers after injection of exogenous IL-33 into infected mice, we thought that its de ciency might compromise the maturation and reproduction of S. mansoni worms. Thus, we compared the morphology and number of worm pairs between IL-33 −/− and WT mice.…”
Section: Resultsmentioning
confidence: 95%
“…1e), indicating that IL-33 may be dispensable for the excretion of schistosome eggs. Because several studies reported a pathogenic role for IL-33 in egg-induced liver pathology by an increased number of liver tissue eggs (25,26), we sought to see whether IL-33 de ciency would be associated with a decreased number of eggs in liver tissues of IL-33 −/− compared to WT mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations